Thermal and geochemical signature of Poás Volcano, Costa Rica (MARCH 2009) - Spampinato, Letizia; Salerno, Giuseppe G.; Martin, Robert S.; Sawyer, Georgina M.; Oppenheimer, Clive; Ilyinskaya, Evgenia; Ramírez, Carlos (Revista geológica de América central, 2009)
.